Association Between Epithelial Cytokines and Clinical Phenotypes of Elderly Asthma - Ulambayar, Bastsetseg; Lee, So-Hee; Yang, Eun-Mi; Ye, Young-Min; Park, Hae-Sim (Allergy, asthma & immunology research, 2019)
Asthma in the elderly has different clinical features including more severe phenotypes with higher comorbidities. Epithelial cells are known to initiate innate/adaptive immune responses in asthmatic airways. We investigated clinical features and epithelial derived cytokine levels in elderly asthmatics compared to non-elderly asthmatics in a cross-sectional cohort of adult asthmatics in order to further understand its pathogenic mechanisms. A total of 1,452 adult asthmatics were enrolled from a single tertiary hospital and were classified into 2 groups: 234 elderly (≥ 60 years at initial diagnosis) and 1,218 non-elderly (< 60 years at initial diagnosis) asthmatics. Asthma-related clinical parameters were compared between the 2 groups. Serum levels of epithelial cell-derived cytokines including interleukin (IL)-31, IL-33, IL-8, eotaxin-2, transforming growth factor beta 1 (TGF-β1) and periostin were measured by enzyme-linked immunosorbent assay. Significantly higher prevalence rates of late-onset asthma (onset age ≥ 40 years) and severe asthma, as well as the lower rate of atopy, blood/sputum eosinophil counts, total immunoglobulin E and eosinophil cationic protein levels were noted in elderly asthmatics compared to non-elderly asthmatics ( < 0.05, respectively). The forced expiratory volume in 1 second (FEV1, % predicted) level tended to be lower in elderly asthmatics ( = 0.07). In addition, serum IL-33 and IL-31 levels were significantly lower in elderly asthmatics, while no differences were found in the serum level of IL-8, eotaxin-2, TGF-β1 or periostin. Among elderly asthmatics, subjects with severe asthma had lower FEV1 (% predicted) value, but showed significantly higher serum levels of eotaxin-2 and TGF-β1, than those with non-severe asthma ( < 0.05 for each). These findings suggest that age-related changes of epithelial cell-derived cytokines may affect clinical phenotypes and severity of elderly asthma: decreased levels of IL-33 and IL-31 may contribute to less Th2 phenotype, while increased levels of eotaxin-2 and TGF-β1 may contribute to severity.